Effect of Visualised Case-Based Learning Strategy On Students' Academic Performance in Chemistry in Ibadan Metropolis, Nigeria - Mabel Ihuoma Idika (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2021)
This study investigated the effect of the use of visualized case-based learning (VCBL) strategy on chemistry students' academic achievement. The theoretical framework for this study is based on Thorndike's idea of transfer of learning. A sample of one hundred and forty-five (145) senior secondary school II chemistry students drawn from four intact classes in two local government areas of Ibadan metropolis, were used for the research. Three well validated instruments were used to collect data. The VCBL package was developed following the Smith and Ragan Instructional System Design (ISD) Model (1999). This model comprises four stages: namely, Analysis, Design, Development and Implementation/Evaluation. Data were analysed by means of inferential statistics (ANCOVA, EMM and Tukey's post-hoc). Results showed that there is significant main effect of treatment on students' achievement in Chemistry (F (2, 248) =17.539; p<0.05; η2=0.124); implying that the posttest scores of students' achievement in achievement significantly differ between the treatment and conventional groups. It was concluded that VCBL strategy has the potential to enable students understand chemistry better by way of promoting transfer of learning. In light of this, implications were discussed and relevant suggestions made.